1974
DOI: 10.1113/jphysiol.1974.sp010476
|View full text |Cite
|
Sign up to set email alerts
|

Actions of glucose and potassium chloride on osmoreceptors slowing gastric emptying

Abstract: SUMMARY1. Five subjects were given 373 test meals of 750 ml. water containing a range of concentrations of glucose or potassium chloride.2. The greater the concentration of solute in the meals, the greater was the volume of the test meal recovered from the stomach after a fixed time.3. When the concentrations of the solutes were expressed as m-osmole/l. corrected by osmotic coefficients based on vapour pressures at 370 C, glucose and potassium chloride were indistinguishable in slowing gastric emptying.4. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1978
1978
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…Stimulation of upper intestinal receptors exerts a potent inhibitory action on gastric emptying via neural and hormonal feedback signals. 27 The gastric emptying of carbohydrates has been suggested to be controlled by intestinal receptors sensitive to both osmotic 28,29 and caloric properties. 30 -32 However, the observation that fructose empties from the stomach more rapidly than equicaloric and equiosmotic glucose loads 11,12 suggests that the Figure 2 Ratings of hunger, fullness and prospective consumption following ingestion of drinks of sucrose, maltose and water control.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of upper intestinal receptors exerts a potent inhibitory action on gastric emptying via neural and hormonal feedback signals. 27 The gastric emptying of carbohydrates has been suggested to be controlled by intestinal receptors sensitive to both osmotic 28,29 and caloric properties. 30 -32 However, the observation that fructose empties from the stomach more rapidly than equicaloric and equiosmotic glucose loads 11,12 suggests that the Figure 2 Ratings of hunger, fullness and prospective consumption following ingestion of drinks of sucrose, maltose and water control.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that the rate of gastric emptying slows in proportion to the osmolality of the gastric contents (Barker et al, 1974 andBrener et al, 1983;Costil and Saltin, 1974;Coyle et al, 1978;Fortran and Ingelfinger, 1968;Foster et al, 1980;Hunt, 1961;Hunt and Knox, 1968;McHugh and Moran, 1979;Moran and McHugh, 1981). However, other studies show no difference in the gastric emptying rates of monosaccaride and polysaccaride solutions of equal concentration (Hunt, 1960;Elias et al, 1968;Foster et al, 1980).…”
Section: Jf Gastricmentioning
confidence: 99%
“…The duodenal osmoreceptor is also supposed to be operated by glucose in its native state (Barker, Cochrane, Corbett, Hunt & Kemp Roberts, 1974). Thus differences between subjects in their gastric emptying of a glucose solution should reflect the between-subject variability in the gastric pumping mechanism and in the inhibitory power of the duodenal osmoreceptor.…”
Section: R a Burn-murdoch And Othersmentioning
confidence: 99%
“…It is known that amino acids slow gastric emptying (Cooke & Moulang, 1972;Barker et al 1977). They probably do so through the osmoreceptor mechanism since amino acids, glucose, and potassium chloride solutions of the same osmolal concentration are equally effective in slowing gastric emptying (Barker et al 1974;Cooke & Moulang, 1972).…”
Section: Gastric Emptying Of Proteinsmentioning
confidence: 99%